The combination of carbonate hydroxyapatite and human β-defensin 3 to enhance collagen fibre density in periodontitis Sprague Dawley rats - Ika Andriani; Edy Meiyanto; S. Suryono; Ika Dewi Ana (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Carbonate hydroxyapatite (CHA) is used as a scaffold to repair bone resorption. Alveolar bone resorption in periodontitis caused by an infection requires the presence of an antibacterial to support bone regeneration. Human β-defensin 3 (HBD3) is an antimicrobial peptide. The local application of the HBD3 antimicrobial is beneficial to inhibiting drug resistance and protecting tissue regeneration against invasive bacteria. Purpose: This study aims to investigate the effect of the administration of a combination of   CHA with HBD3 on the collagen density of periodontitis rats (Sprague Dawley). Methods: This study was a true experimental study with a post-test control group design. Thirty-two Sprague Dawley animal models were randomly blind selected placed under anaesthetic, then a 2-mm silk ligature was attached as a ligation to the mandibular incisors for 14 days in order to generate periodontitis. The study subjects were divided into two groups, the group with CHA and CHA loaded HBD3 (CHA + HBD3) implantation. On days 7, 14, 21 and 28, four rats were taken randomly from each group for decapitation, followed by histological processing and examination with trichome Mallory staining. The data was analysed using the Kruskal Wallis test (p<0.05). Results: An increase in collagen density during the healing process was found. There was a significant difference between CHA and CHA+HBD (p=0.004 and p=0.008; p<0.05) in collagen density between the groups. Conclusion: The combination of CHA and HBD3 can enhance the collagen density in periodontitis Sprague Dawley rats, compared to CHA only groups.